Understanding socially responsible investing and its implications for islamic investment industry / Mohd Nizam Barom. - Barom, Mohd Nizam (Universiti Teknologi Mara Selangor, 2019)
Social, ethical and environmental concerns have been used as important consideration for investment decision by an increasing number of investors. This can be seen by the size and growth of the socially responsible investment (SRI) industry in the developed economies. At the same time, scholars and commentators of Islamic finance have also called for Islamic investment industry to learn from the experience of SRI in incorporating social responsibility issues in the investment process, in line with the ethical principles of Islam and the overall objective of the Shari'ah (Maqasid al-Shari'ah). This would require Islamic investment sector to have a clear understanding of the SRI industry in order to effectively benefit from its experience. This is particularly critical due to the significant diversity of investors and complexity in the issues and strategies adopted in the SRI industry. Hence, this paper adds to the Islamic investment literature by providing an extensive and systematic survey of SRI industry in terms of its (i) underlying motivations and values; (ii) issues of concerns; (iii) types of investors; and (iv) screening strategies. It then synthesizes these components within the context of the 'value-based' investors. This synthesized framework offers a useful tool for Islamic investment practitioners to understand the theoretical and practical aspects of SRI. Subsequently, the paper highlights important implications of the findings for Islamic investment industry in terms of the issues that it needs to consider in emulating SRI practices and a number of lessons that it can learn from the SRI experience.